Carbapenem-Resistant E. cloacae in Southwest China: Molecular Analysis of Resistance and Risk Factors for Infections Caused by NDM-1-Producers - Jia, Xiaojiong; Dai, Wei; Ma, Weijia; Yan, Jinrong; He, Jianchun; Li, Shuang; Li, Congya; Yang, Shuangshuang; Xu, Xiuyu; Sun, Shan; Shi, Jing; Zhang, Liping (Frontiers in Microbiology, 2018)
Carbapenem-resistant Enterobacteriaceae (CRE) has been considered a serious global threat, but carbapenem resistance remains relatively uncommon in E. cloacae, especially in China. The aim of this study was to characterize carbapenem-resistant E. cloacae (CR-ECL) isolates from 2012 to 2016 in Southwest China. Our study revealed that 20 (15.2%) of the 132 CR-ECL isolates obtained from patients were identified as NDM-1, with most isolates carrying the IncFIIA plasmids. Notably, we initially observed that the E. cloacae strain co-harbored NDM-1 and IMP-8 carbapenemases simultaneously. Analysis of the genetic environment of these two genes has revealed that the highly conserved regions (blaNDM-1-bleMBL-trpF-tat) are associated with the dissemination of NDM-1, while IS26, intI1, and tniC could be involved in the spread of IMP-8. Molecular epidemiology studies showed the nosocomial outbreak caused by NDM-1-producing E. cloacae ST88. Transferring from another hospital and previous carbapenem exposure were identified as independent risk factors for the acquisition of NDM-1-producing E. cloacae. These findings emphasize the need for intensive surveillance and precautions to monitor the further spread of NDM-1 in China.